1994
DOI: 10.1111/j.1476-5381.1994.tb16191.x
|View full text |Cite
|
Sign up to set email alerts
|

BMS‐180560, an insurmountable inhibitor of angiotensin II‐stimulated responses: comparison with losartan and EXP3174

Abstract: 1 This study compares the activity of BMS-180560 (2-butyl-4-chloro-1-[[1-[2-(2H-tetrazol-5-yl)phenyl]-1H-indol-4-yl]methyl]-lH-imidazole-5-carboxylic acid), an insurmountable angiotensin II (All) receptor antagonist, with that of losartan and EXP3174 in functional and biochemical models of AII-receptor activation.2 BMS-180560 selectively inhibited ['25I]-Sar'Ile8AII (['25I]SI-AII) binding to rat aortic smooth muscle (RASM) cell and rat adrenal cortical AT, receptors (Ki = 7.6 ± 1.2 and 18.4 ± 3.9 nM respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…This, in turn, triggers cell growth and constriction (Vincentini & Villereal, 1986). The initial AT 1 receptor-evoked responses can conveniently be measured in primary cell cultures and in cell lines (Dickinson et al, 1994;Koh et al, 1994;Panek et al, 1995;Perlman et al, 1995;Balmforth et al, 1997) and appear to be common to the biological actions of angiotensin II. In addition, it was also observed by Dickinson et al (1994) that angiotensin II increases the rate at which rabbit aortic smooth muscle cells acidify their environment with products of their energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, in turn, triggers cell growth and constriction (Vincentini & Villereal, 1986). The initial AT 1 receptor-evoked responses can conveniently be measured in primary cell cultures and in cell lines (Dickinson et al, 1994;Koh et al, 1994;Panek et al, 1995;Perlman et al, 1995;Balmforth et al, 1997) and appear to be common to the biological actions of angiotensin II. In addition, it was also observed by Dickinson et al (1994) that angiotensin II increases the rate at which rabbit aortic smooth muscle cells acidify their environment with products of their energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The initial AT 1 receptor-evoked responses can conveniently be measured in primary cell cultures and in cell lines (Dickinson et al, 1994;Koh et al, 1994;Panek et al, 1995;Perlman et al, 1995;Balmforth et al, 1997) and appear to be common to the biological actions of angiotensin II. In addition, it was also observed by Dickinson et al (1994) that angiotensin II increases the rate at which rabbit aortic smooth muscle cells acidify their environment with products of their energy metabolism. This latter response is commonly observed for G-protein coupled receptors and it is claimed to occur irrespective of the initial cellular events (McConnell et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, Sachinidis et al concluded that EXP3174 is a more potent angiotensin AT, receptor antagonist than is losartan in blocking angiotensin 11-induced cellular responses. Dickinson et al also reported that EXP3 174 noncompetitively inhibited angiotensin 11-stimulated phosphoinositide turnover in rat aorta smooth muscle cells (16).…”
Section: Angiotensin I1 Antagonism Properties In Vitromentioning
confidence: 99%
“…Human AT 1 receptor affinity was determined using a previously described standard binding assay (Dickinson et al, 1994). Human recombinant AT 1 receptor membranes (catalog no.…”
Section: Radioligand Binding Studiesmentioning
confidence: 99%
“…The membranes were incubated for 60 min at 37°C. Bound and free radioligand were separated and counted as described previously (Dickinson et al, 1994).…”
Section: Radioligand Binding Studiesmentioning
confidence: 99%